Fitness weight training - Baechle, Thomas R. 1943-; Earle, Roger W. 1967-
Whether you're a regular at the gym or just getting started, here are proven program for attaining the body you want! Provides an overview of weight training, from equipment selection to technique, to help you get to work quickly, safely, and correctly.